2018
DOI: 10.1111/jonm.12698
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nurses’ willingness to lead

Abstract: Aim To identify factors influencing nurses’ willingness to lead. Background Given the ageing workforce and the projected retirement of nurse leaders, there is a concern about nursing leadership shortages in the next decade. Several studies have shown that nurses are not interested in pursuing leadership positions, but studies investigating nurses’ willingness to lead and related predictors remain limited. Methods A workforce survey of 1,201 direct‐care nurses was conducted in Oregon. Logistic regression modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 16 publications
7
24
1
Order By: Relevance
“…Previous research identified nurses' willingness to lead and leadership self‐efficacy as significant determinants of nurses' leadership abilities and effectiveness (Abou, 2017); hence, our findings underscore the greater need for bolstering nurses' belief in their leadership ability and their motivation to lead, through relevant training and professional advancement, theory‐driven interventions and a supportive leadership. Meanwhile, nurses in this study perceive their nurse managers as highly authentic and their work environment as highly favourable, which are in accordance with local (Al Sabei et al, 2019; Labrague et al, 2021) and international research (Raso et al, 2020; Valle et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous research identified nurses' willingness to lead and leadership self‐efficacy as significant determinants of nurses' leadership abilities and effectiveness (Abou, 2017); hence, our findings underscore the greater need for bolstering nurses' belief in their leadership ability and their motivation to lead, through relevant training and professional advancement, theory‐driven interventions and a supportive leadership. Meanwhile, nurses in this study perceive their nurse managers as highly authentic and their work environment as highly favourable, which are in accordance with local (Al Sabei et al, 2019; Labrague et al, 2021) and international research (Raso et al, 2020; Valle et al, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…The scale's items were answered using a 5‐point Likert frequency scale (1 for strongly disagree to 5 for strongly agree ). The scale was found reliable and valid based on the previous research, with an internal consistency value of 0.78 (Al Sabei et al, 2019; Mascia et al, 2015).…”
Section: Methodsmentioning
confidence: 80%
“…Based on the PES‐NWI composite score, we recategorized work environments as favorable (if four or five subscales had scores exceeding the theoretical midpoint of 2.5), mixed (two or three subscales had scores exceeding 2.5), or unfavorable (one or none of the subscales had scores exceeding 2.5). The use of the 2.5 theoretical midpoint is consistent with recent literature (Al‐Hamdan et al, ; Al Sabei, Ross, & Lee, ) and has been empirically confirmed through latent class analysis and supported by criterion validity (Lake & Friese, ).…”
Section: Methodssupporting
confidence: 85%
“…Moreover, providing adequate organizational support for new nurses undertaking leadership roles is important. Al Sabei et al () found that nurses’ perceptions of leadership preparedness was associated positively with their willingness to engage in new leadership roles. Interestingly, expatriate nurses were less likely to leave their job compared to Omani nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence demonstrated links between NWE and patient outcomes, including patient satisfaction (Lake et al 2019), and nurse outcomes including NJS (Nantsupawat et al 2017) and willingness to lead (Al Sabei et al 2019). In the Eastern Mediterranean, the topic of NWE has recently gained increasing recognition.…”
Section: Introductionmentioning
confidence: 99%